2019
DOI: 10.3390/w11020257
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Deformity of Scoliosis in Gilthead Seabreams (Sparus aurata): Association with Changes to Calcium-Phosphor Hydroxyapatite Salts and Collagen Fibers

Abstract: The development of skeletal deformities in seabream farming affects fish growth, survival, and production costs. Collagen distribution in different fish tissues might be correlated with swimming behavior. This study investigates whether scoliosis in seabreams is associated with changes to calcium-phosphor hydroxyapatite salts and collagen fibril morphology. Samples of decalcified vertebrae of scoliotic and non-scoliotic seabreams were examined with transmission electron microscopy and collagen micrographs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…This result demonstrated that the presence of a vertebral anomaly affects at a transcriptional level not only locally the malformed part of the tissue, but also the expression pattern of the entire column. Similarly, Boursiaki et al (2019) observed recently that the presence of scoliosis in gilthead sea bream is more frequent in the caudal region, but in those malformed fish, both the caudal and abdominal vertebrae were significantly shorter when compared to the vertebrae of a normal fish. In other studies, with Salmonidae species, malformed vertebrae have been shown to have comparable mineral content to normal vertebrae, even if differences existed at an earlier stage of the malformation process (Fjelldal et al, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…This result demonstrated that the presence of a vertebral anomaly affects at a transcriptional level not only locally the malformed part of the tissue, but also the expression pattern of the entire column. Similarly, Boursiaki et al (2019) observed recently that the presence of scoliosis in gilthead sea bream is more frequent in the caudal region, but in those malformed fish, both the caudal and abdominal vertebrae were significantly shorter when compared to the vertebrae of a normal fish. In other studies, with Salmonidae species, malformed vertebrae have been shown to have comparable mineral content to normal vertebrae, even if differences existed at an earlier stage of the malformation process (Fjelldal et al, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…Lall [15] reported that the calcium-to-phosphorus ratio in fish bones ranges from 0.7 to 1.6. The Ca/P ratio for sea bream individuals ranges from 1.79 to 2.36 [5,6,16]. According to Song et al [29] (2017) the Ca/P ratio for Japanese seabass with a mean weight of 12.5 g ranged from 1.71 to 1.79.…”
Section: Discussionmentioning
confidence: 99%
“…It includes bones, cartilage, scales, teeth, connective tissue, fin rays, tendons and all the associated stem cells [2]. The axial skeleton is made up of bones and cartilage, acts as a support for body muscles, protects organs and plays an important role in the metabolism of calcium as a source of stored ions [4][5][6]. The axial skeleton is structurally varied from a cartilage that encloses the notochord to a fully ossified vertebral column in the teleosts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various other procedures have also been used in scientific studies, such as X‐ray imaging, double staining or even computer tomography; (Boglione & Costa, 2011; Ortiz‐Delgado et al., 2014). X‐ray imaging, is a common method to detect skeletal deformities in fish (Afonso et al., 2000; Boursaki et al., 2019; Korkut et al., 2009), but mostly used in scientific research.…”
Section: Introductionmentioning
confidence: 99%